CREACIÓN DEL REGISTRO NACIONAL DE IDENTIFICACIÓN GENÉTICA DELINCUENCIAL EN EL ECUADOR - Ruiz Rojas, Hernán Manuel (2016)
At the present time, the historical reality that the Ecuadorians are living, demands immediate reactions on behalf of the Ecuadorian State to knock down the delinquency. This reaction should be carried out with the immediate modernization and the implementation of new technologies to the Prosecutor's office, and to improve this way the Procedural Penal System. This way to strengthen the activity of the State, dedicated to the penal clarification of the illicit ones, it is necessary to grant to the organs of penal persecution, a tool of high effectiveness, in the execution of the penalization and prevention of the crime. It is this indispensable way to take advantage of to the maximum the tools that he/she offers the technology of vanguard, as it is it the determination of DNA for the construction of the genetic print whose particular level of dependability will allow to obtain overwhelming test to accuse or to acquit people syndicated as responsible, not only of crimes against the sexual integrity but of other crimes, in the course of which biological samples had been left as rakes. It is here that the creation of a Registration of Genetic Identification Delincuencial, is fundamental for that indicated in next previous paragraph, which will be orchestrated as a database that consigns all genetic print associated to an evidence obtained in the different scenes of the crime or in the garments of the victims, or come from the genetic profiles made in the course of judicial processes by order of the tribunals interveners or of the Prosecutor's office. 5 This way, the initiative of creating a National Registration of criminal reliable Genetic Identification, in which you/they appear identified, so much the most dangerous criminals, as people that have been declared penally responsible for a jurisdictional organ and by means of it sentences strong and irrevocable, without conculcar individual guarantees and starting from the beginning of the imposition of the corresponding pain, what would grant artificial certainty to people that having been processed, was not declared responsible for the facts that were imputed, reinstating them from a more prompt way to the productive national life